2016
DOI: 10.1016/j.ajhg.2016.08.018
|View full text |Cite
|
Sign up to set email alerts
|

GCM2 -Activating Mutations in Familial Isolated Hyperparathyroidism

Abstract: Primary hyperparathyroidism (PHPT) is a common endocrine disease characterized by parathyroid hormone excess and hypercalcemia and caused by hypersecreting parathyroid glands. Familial PHPT occurs in an isolated nonsyndromal form, termed familial isolated hyperparathyroidism (FIHP), or as part of a syndrome, such as multiple endocrine neoplasia type 1 or hyperparathyroidism-jaw tumor syndrome. The specific genetic or other cause(s) of FIHP are unknown. We performed exome sequencing on germline DNA of eight ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
144
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(152 citation statements)
references
References 44 publications
2
144
0
6
Order By: Relevance
“…Recently, activating mutations of the glial cells missing 2 ( GCM2 ) gene, located on chromosome 6p24.2, have been reported in FIHP patients (Guan et al., ). GCM2 encodes a protein that acts as a transcription factor regulating parathyroid development and may also act to regulate the effect of calcium on PTH expression and secretion by parathyroid cells (Kamitani‐Kawamoto et al., ; Han, Tsunekage, & Kataoka, ).…”
Section: Syndromic and Hereditary Forms Of Parathyroid Carcinomamentioning
confidence: 99%
“…Recently, activating mutations of the glial cells missing 2 ( GCM2 ) gene, located on chromosome 6p24.2, have been reported in FIHP patients (Guan et al., ). GCM2 encodes a protein that acts as a transcription factor regulating parathyroid development and may also act to regulate the effect of calcium on PTH expression and secretion by parathyroid cells (Kamitani‐Kawamoto et al., ; Han, Tsunekage, & Kataoka, ).…”
Section: Syndromic and Hereditary Forms Of Parathyroid Carcinomamentioning
confidence: 99%
“…Identification of the susceptibility gene for the hyperparathyroidism-jaw tumor syndrome by a positional cloning approach has shown that germline mutations in the CDC73 gene are causative for parathyroid cancer (Carpten, et al 2002; Shattuck, et al 2003). An exome sequencing approach has shown that germline activating mutations in the GCM2 gene occur in 18% of FIHP kindreds (Guan, et al 2016). Germline mutations in the AIP tumor suppressor gene identified by a positional cloning approach, which is also located on 11q13, occur in 20% of FIPA patients and in 30–50% of patients with familial acromegaly, and germline GPR101 microduplication or mutation occurs in patients with X-linked acrogigantism (X-LAG) (Daly, et al 2007; Trivellin, et al 2014; Vierimaa, et al 2006).…”
Section: Men1-like Disease From Germline Mutation In Men1 or Other Sumentioning
confidence: 99%
“…There are also other autosomal dominant genetic forms of familial hypercalcaemia, which are associated with different syndromic manifestations such as tumours and particularly hyperparathyroidism linked to tumour suppressor gene mutations, including:the MEN1 gene, coding for menin in multiple endocrine neoplasia type 1 (MEN1),the HRPT2 (/CDC73) gene , specifically involved in carcinogenesis,the CDKN1B gene , but also the APC, SFRPs, GSK3β, RASSF1A, HIC1, RIZ1, and WT1 genes, and possibly CASR [28], GNA11 , AP2S1, and GCM2 or glial cells Missing-2, a transcription factor linked to the early development pf parathyroid glands [1, 29]as well as mutations of proto-oncogenes ( CCND1/PRAD1 , RET in MEN2, ZFX , CTNNB1 , EZH2 ) [3032]. …”
Section: Genetic Causesmentioning
confidence: 99%
“…but also the APC, SFRPs, GSK3β, RASSF1A, HIC1, RIZ1, and WT1 genes, and possibly CASR [28], GNA11 , AP2S1, and GCM2 or glial cells Missing-2, a transcription factor linked to the early development pf parathyroid glands [1, 29]…”
Section: Genetic Causesmentioning
confidence: 99%